CACHIMBO GUARANI DO SÍTIO ARQUEOLÓGICO MACACO, ESTADO DE SÃO PAULO - BARROCÁ FACCIO, Neide; DI BACO, Hiuri Marcel (Revista Tópos, 2013)
Os cachimbos em sítios arqueológicos guarani do Estado de São Paulo são raros e apresentam diferentes formas. São confeccionados em argila. O tipo de antiplástico utilizado em cachimbos pré-coloniais ainda foi pouco estudado. O cachimbo evidenciado no Sítio Arqueológico Macaco apresenta-se numa forma confeccionada por modelagem e acordelado. Chama atenção a decoração incisa presente em toda a sua superfície. Palavras-chave: guarani, cachimbo guarani, cerâmica guarani. GUARANI PIPE MACACO ARCHAEOLOGICAL SITE, STATE OF SAO PAULO Abstract The guarani pipes in archaeological sites in the State of São Paulo are rare and have different forms. They are made out of clay. The type of anti-plastic used in pre-colonial have yet been little studied. The pipe shown in the Archaeological Site Macaco presents it is a form built by the technique of overlapping small ropes of clay superimposed on each other. It draws attention to the incisive decoration present throughout its surface. Keywords: guarani, guarani pipe, guarani pottery.